Insighting Drivers of Population Exposure to Ambient Ozone (O3) Concentrations across China Using a Spatiotemporal Causal Inference Method - Junming Li; Jing Xue; Jing Wei; Zhoupeng Ren; Yiming Yu; Huize An; Xingyan Yang; Yixue Yang (Remote Sensing, 2023)
Ground-level ozone (<semantics>O3</semantics>) is a well-known atmospheric pollutant aside from particulate matter. China as a global populous country is facing serious surface <semantics>O3</semantics> pollution. To detect the complex spatiotemporal transformation of the population exposure to ambient <semantics>O3</semantics> pollution in China from 2005 to 2019, the Bayesian multi-stage spatiotemporal evolution hierarchy model was employed. To insight the drivers of the population exposure to ambient <semantics>O3</semantics> pollution in China, a Bayesian spatiotemporal LASSO regression model (BST-LASSO-RM) and a spatiotemporal propensity score matching (STPSM) were firstly applied; then, a spatiotemporal causal inference method integrating the BST-LASSO-RM and STPSM was presented. The results show that the spatial pattern of the annual population-weighted ground-level <semantics>O3</semantics> (<semantics>PWGLO3</semantics>) concentrations, representing population exposure to ambient <semantics>O3</semantics>, in China has transformed since 2014. Most regions (72.2%) experienced a decreasing trend in <semantics>PWGLO3</semantics> pollution in the early stage, but in the late stage, most areas (79.3%) underwent an increasing trend. Some drivers on <semantics>PWGLO3</semantics> concentrations have partial spatial spillover effects. The <semantics>PWGLO3</semantics> concentrations in a region can be driven by this region’s surrounding areas’ economic factors, wind speed, and <semantics>PWGLO3</semantics> concentrations. The major drivers with six local factors in 2005–2014 changed to five local factors and one spatial adjacent factor in 2015–2019. The driving of the traffic and green factors have no spatial spillover effects. Three traffic factors showed a negative driving effect in the early stage, but only one, bus ridership per capita (BRPC), retains the negative driving effect in the late stage. The factor with the maximum driving contribution is BRPC in the early stage, but <semantics>PM2.5</semantics> pollution in the late stage, and the corresponding driving contribution is 17.57%. Green area per capita and urban green coverage rates have positive driving effects. The driving effects of the climate factors intensified from the early to the later stage.